No Added Neuroprotective Effect of Remote Ischemic Postconditioning and Therapeutic Hypothermia After Mild Hypoxia-Ischemia in a Piglet Model - Andelius, Ted C. K.; Pedersen, Mette V.; Andersen, Hannah B.; Andersen, Mads; Hjortdal, Vibeke E.; Pedersen, Michael; Ringgaard, Steffen; Hansen, Lærke H.; Henriksen, Tine B.; Kyng, Kasper J. (Frontiers in Pediatrics, 2020)
Introduction: Hypoxic ischemic encephalopathy (HIE) is one of the major causes of death and disability in children worldwide. Apart from supportive care, the only established treatment for HIE is therapeutic hypothermia (TH). As TH is only partly neuroprotective; there is a need for additional therapies. Intermittent periods of limb ischemia, called remote ischemic postconditioning (RIPC), have been shown to be neuroprotective after HIE in rats and piglets. However, it is unknown whether this treatment will add to the neuroprotective effect of TH. In a piglet model of HIE we tested whether there was an added neuroprotective effect of combining RIPC with TH compared to TH alone measured by magnetic resonance imaging and spectroscopy (MRI/MRS). Methods: Thirty-two piglets were subjected to a global hypoxic-ischemic insult. Twenty-six animals were randomized to TH alone or RIPC plus TH, and six animals were subjected to hypoxia-ischemia only. TH was whole-body cooling. RIPC was induced one hour after hypoxia-ischemia by four cycles of five minutes of ischemia and five minutes of reperfusion on both hind limbs. The primary outcome was Lac/NAA ratio at 24 hours measured by MRS. Secondary outcomes were NAA/Cr, diffusion weighted imaging, arterial spin labeling, and blood oxygen dependent signal measured by MRI/MRS at 6, 12, and 24 hours after the hypoxic-ischemic insult as well as aEEG score. Results: All three groups were subjected to a comparable, but mild insult. There was no difference between the two intervention groups in Lac/NAA ratio, NAA/Cr ratio, diffusion weighted imaging, arterial spin labeling, or blood oxygen dependent signal. Animals receiving supportive care only, had lower NAA/Cr ratio at 24 hours compared to the two intervention groups. There was no overall difference in aEEG score between the three groups. Conclusion: Treatment with RIPC resulted in no additional neuroprotection when combined with TH after a mild insult. The added neuroprotective effect of RIPC after a more severe insult remains to be elucidated.